Novo gênero de Calliini (Coleoptera, Cerambycidae, Lamiinae) - Galileo, Maria Helena M.; Martins, Ubirajara R. (Papéis Avulsos de Zoologia, 2010)
Paradrycothaea gen. nov. (Calliini, Lamiinae) is erected to two Mexican species: P. pilosicornis sp. nov., type species, from Quintana Roo and P. jamesi sp. nov. from Chiapas.